PENGARUH PENGELOLAAN DANA DESA, TRANSPARANSI, DAN PARTISIPASI TERHADAP KESEJAHTERAAN MASYARAKAT DESA MANGGIS KECAMATAN PUNCU KABUPATEN KEDIRI - Pujiningtyas, Manik Lelibid; Solikah, Mara’tus; Winarko, Sigit Puji (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the influence of village fund management, transparency, and community participation on community welfare in Manggis Village, Puncu District, Kediri Regency. The background of the study is based on the importance of accountable and participatory village finances to support future village development and improve community cohesion. This type of research uses an associative quantitative approach, with the population of the entire Manggis Village community involved in the management and receipt of village fund benefits. The research sample was created using the Slovin formula, and data were obtained using a Likert scale. The data analysis technique used was multiple linear regression analysis to understand the impact of independent variables on the dependent variable, both in parallel and simultaneously. The results of the study indicate that village fund management, transparency, and community participation have a positive and significant effect on community welfare. This indicates that the better the management and transparency of village funds and the higher the level of community participation, the better the community welfare in Manggis Village.